PERANAN PENYULUH PERTANIAN LAPANGAN (PPL) SEBAGAI KOMUNIKATOR PEMBANGUNAN TERHADAP KELOMPOK TANI - Arifin Sugianto (JURNAL LENSA MUTIARA KOMUNIKASI, 2017)
This study aims to look at how the role of field agricultural instructor as a developmentcommunicator to farmer groups in Desa Merdeka, Kecamatan Simpang Empat, KabupatenTanah Karo. Samples were taken from six farmer groups with non-probability samplingtechnique by purposive sampling and involve 60 respondents. Data were obtained from aquestionnaire consisting of 21 questions, plus data from some interviews result. Analysis ofdata using a single table analysis techniques. research shows that the education activities canincrease farmer knowledge and further could boost agricultural production, become welfarefarmers. In house training and field extension visits need to be improved because the visitfrequency is very low. The counseling methods applied usually lectures, props and practice.Local languages often used in the process of counseling.